2019
DOI: 10.1039/c8nr07862a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene–Si CMOS oscillators

Abstract: The ambipolarity of graphene is exploited to realize a new class of electronic oscillators by integrating a graphene field-effect transistor with Si CMOS logic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These issues arise because graphene has zero bandgap characteristics [3]. Nevertheless, even with much lower , by taking advantage of the graphene's ambipolar conduction, frequency multipliers and oscillators have been successfully demonstrated, proving that GFETs are also suitable for use as the transistor in RF components [18,32,33].…”
Section: Figures Of Merit (mentioning
confidence: 99%
See 2 more Smart Citations
“…These issues arise because graphene has zero bandgap characteristics [3]. Nevertheless, even with much lower , by taking advantage of the graphene's ambipolar conduction, frequency multipliers and oscillators have been successfully demonstrated, proving that GFETs are also suitable for use as the transistor in RF components [18,32,33].…”
Section: Figures Of Merit (mentioning
confidence: 99%
“…Oscillators are used in electronic devices to produce a periodic oscillating signal. Recently, a GFET-based oscillator was developed in 2019 by Gilardi and his research group [18]. The oscillator is realized by integrating a top- gated GFET with an Si CMOS D latch and timing RC circuit.…”
Section: A Oscillatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in this context, graphene [8][9][10][11][12][13][14] can be envisaged as a potential interconnect which could replace copper. Moreover, graphene is projected to be an excellent candidate material for interconnects due to its high carrier mobility ( × 2 10 5 cm 2 /V-s) 15 , ballistic transport 16 , high current carrying capacity 17 and high thermal conductivity 18 .…”
mentioning
confidence: 99%
“…Huang et al ( 2014 ) constructed a low-temperature hybrid integrated circuit where graphene devices and Si-CMOS circuits integrated together. Gilardi et al ( 2019 ) designed relaxation oscillators using a GFET, Si CMOS D latch, and timing RC circuit. It is observed that the introduction of graphene material in the Si-CMOS logic circuit has improved the circuit complexity and also added other device functionality.…”
Section: Cmos Compatibilitymentioning
confidence: 99%